Dietary methionine supplementation improves cognitive dysfunction associated with transsulfuration pathway upregulation in subacute aging mice - Yuncong Xu; Yuhui Yang; Yonghui Shi; Bowen Li; Yanli Xie; Guowei Le (npj Science of Food)
Abstract To explore the effects of methionine (Met) supplementation on cognitive dysfunction and the associated mechanisms in aging mice. The mice were administrated 0.15 g/kg/day D-galactose subcutaneously and fed a normal (0.86% Met) or a Met-supplemented diet (1.72% Met) for 11 weeks. Behavioral experiments were conducted, and we measured the plasma metabolite levels, hippocampal and plasma redox and inflammatory states, and hippocampal transsulfuration pathway-related parameters. Met supplementation prevented aging-induced anxiety and cognitive deficiencies, and normalized the plasma levels of multiple systemic metabolites (e.g., betaine, taurine, and choline). Furthermore, dietary Met supplementation abolished oxidative stress and inflammation, selectively modulated the expression of multiple cognition-related genes and proteins, and increased flux via the transsulfuration pathway in the hippocampi of aging mice, with significant increase in H2S and glutathione production. Our findings suggest that dietary Met supplementation prevented cognitive deficiencies in aging mice, probably because of increased flux via the transsulfuration pathway.